Spatial distribution and temporal progress of Huanglongbing in areas with strict disease management - Pazolini, Kelly (2019)
Citriculture is an important agroindustrial activity for Brazil and citrus production is concentrated in São Paulo State. However, the activity is facing a Huanglongbing (HLB) epidemic which is considered to be the main threat to global citrus production. In spite of many management efforts, the incidence of HLB continues to increase since its detection in São Paulo State, in 2004. The difficulty of handling HLB is associated with the migration of the vector, Diaphorina citri, which acquires the bacteria in external inoculum sources and the limited effect of the strict HLB management performed by farms (eradication of symptomatic trees and frequent vector control) on the primary dissemination of the disease. Thus, epidemiological studies can facilitate the understanding of the complex pathosystem and help in the decision of more efficient control measures. The objectives of this study were: 1) to determine the spatial pattern of HLB in 24 citrus blocks under strict management of the disease and 2) to study the temporal progress of the disease and the spatial distribution of HLB and the vector in a large scale property that carried out the strict management of the disease and its association with external inoculum sources. To verify the spatial pattern of HLB, modified Ripley\'s K-function and kernel density estimation maps were used. The results showed that the regular distribution pattern of HLB symptomatic trees prevailed in the blocks studied and a weak aggregation of approximately 58 m was observed at the edges of the blocks. The largest aggregation distances and averages of D. citri/trap occurred in blocks located at the periphery of the properties. The regular spatial pattern and the concentration of disease and vector in the periphery of the properties evidenced the importance of primary dissemination. For the study of the disease temporal progress, the Gompertz and logistic models were adjusted to the annual progress of HLB for 177 blocks. The distribution of HLB progress rates and incidence (for 177 blocks) and average D. citri/trap (for 296 blocks) were visualized on gradient maps. The disease progress rate values obtained with the Gompertz model (0.04 to 0.28 per year), average HLB incidence (0.11) and average D. citri/trap (0.016) were low compared with literature data. The variables presented the highest values for blocks located at the periphery of the property, rather than for blocks surrounded by citrus. Many noncommercial plants, potentially serving as source of inoculum, were found near blocks with the highest rates of disease progress, HLB incidence and average D. citri/trap. The results demonstrated the importance of primary dissemination in areas that carry out a strict HLB management. Therefore, in order to reduce new infections, HLB management must effectively reduce external sources of inoculum and regional management should include, in addition to commercial orchards, noncommercial plants.